Tie the knot - a step by step wedding planner - Alex Arvin S Susaipillai (2018)
Creating the perfect wedding is a dream. However, the prohibitive cost for wedding planners poses as a hindrance. The invention is aimed at building a web application to solve the needs of couples who are planning their wedding. The application serves as an all-in-one-stop wedding planning tool kit for a successfully and well-organized wedding. A user account will be shared between the bride and groom to plan the wedding in an interactive and collaborative environment. The creation comprises essential management tools such as wedding checklist, reminders, budget tracker, guestlist, online electronic invitation and RSVP system with SMS function, seating plan, calendar function, vendor list, pin board, wedding day scheduler and chat function